ATF2 loss promotes 5-FU resistance in colon cancer cells via activation of the ATR-Chk1 damage response pathway - Yang, Hao; Hübner, Kerstin; Hampel, Chuanpit; Erlenbach-Wünsch, Katharina; Selvamani, Selva Babu; Shukla, Vikas; Geppert, Carol-Immanuel; Hartmann, Arndt; Mahadevan, Vijayalakshmi; Schneider-Stock, Regine (BMC Cancer, 2023)
Background: The role of ATF2 in colon cancer (CC) is controversial. Recently, we reported that low ATF2 expression is characteristic of highly invasive tumors, suggesting that ATF2 might also be involved in therapy resistance. 5-Fluorouracil (5-FU) is the best-known chemotherapeutic drug for CC, but drug resistance affects its curative effect. To date, the role of ATF2 in the 5-FU response remains elusive. Methods/Results: For our study, we had available HCT116 cells (wild-type p53) and HT29 colon tumor cells (mutant p53) and their corresponding CRISPR‒Cas9-generated ATF2-KO clones. We observed that loss of ATF2 triggered dose- and time-dependent 5-FU resistance in HCT116 cells by activating the DNA damage response (DDR) pathway with high p-ATRThr1989 and p-Chk1Ser317 levels accompanied by an increase in the DNA damage marker γ-H2AX in vitro and in vivo using the chicken chorioallantoic membrane (CAM) model. Chk1 inhibitor studies causally displayed the link between DDR and drug resistance. There were contradictory findings in HT29 ATF2-KO cells upon 5-FU exposure with low p-Chk1Ser317 levels, strong apoptosis induction, but no effects on DNA damage. In ATF2-silenced HCT116 p53−/− cells, 5-FU did not activate the DDR pathway. Co-immunoprecipitation and proximity ligation assays revealed that upon 5-FU treatment, ATF2 binds to ATR to prevent Chk1 phosphorylation. Indeed, in silico modelling showed reduced ATR-Chk1 binding when ATF2 was docked into the complex. Conclusions: We demonstrated a novel ATF2 scaffold function involved in the DDR pathway. ATF2-negative cells are highly resistant due to effective ATR/Chk1 DNA damage repair. Mutant p53 seems to overwrite the tumor suppressor function of ATF2.
CRIS-Team Scopus Importer:2023-06-30
Keywords: ATR kinase; CAM model; DDR; DNA repair; γ-H2AX